Did Previous EU Enlargements Change the Regional Distribution of Production? An Empirical Analysis of Three Enlargement Episodes - Peter Huber (Austrian Institute of Economic Research (WIFO), 2007)
This paper analyses the effects of previous enlargements of the European Union on the regional structure of production. Focusing on regional development five years before and seven years after integration, we find relatively small and heterogeneous effects. For the addition of Greece a robust tendency of decentralisation is found. For Southern enlargement effects on border regions are significant for wages and employment and for Northern enlargement no significant effects are found. Finally, for nearby old member states results are contradictory and are not robust to correcting for potential bias arising from serial autocorrelation of the error term.
Keywords: 330; EU-Accession; Regional Effects of Integration; EU-Mitgliedschaft; Wirtschaftliche Anpassung; Wirtschaftswachstum; Räumliche Arbeitsteilung; Griechenland; Spanien; Portugal; Österreich; Schweden; Finnland; EU-Staaten